The Innovative Ways of Development in the Oil and Gas Industry of Kazakhstan - Beisembekova, Sabina; Sikhimbayev, Muratbay; Sikhimbayeva, Dinar; Srailova, Gulnara (International Journal of Energy Economics and Policy, 2022)
The article considers theoretical and methodological approaches to research of sustainable development of the oil and gas industry of Kazakhstan in modern conditions. Oil and gas industry is viewed as one of the priority directions of government economic policy, which is of particular importance in providing sustainable development of the country. It is noted, that increasing of stability of Kazakhstani oil and gas industry development is presented itself one of the most important issue of state economics. Authors identify main problems affecting on innovative development of the oil and gas industry. It was emphasized, taking into account the current trends, stability of oil and gas complex is affected by the number of conjuncture market factors, including price factors, bank interest rates, market conjuncture for this product, or value of its supply and demand in domestic and foreign markets. Main principles and criteria of innovative development of the oil and gas industry were developed. It is proved, that innovative development of the oil and gas industry should be carried out on the basis of the principles. The forecast of innovative development of the oil and gas industry was built on the basis of designed formula. The forecast of revenue from innovations is on the perspective period in the extraction and processing of high-sulfur, light and heavy oil for 2022-2026 that presented as table and forecast diagram. The innovative development of the oil and gas industry should be carried out on the basis of the researched principles. As a result of conducted research priorities of innovative development of the oil and gas industry were identified.